Too much for your own good: Excessive dopamine damages neurons and contributes to Parkinson's disease: An Editorial Highlight for "Enhanced tyrosine hydroxylase activity induces oxidative stress, causes accumulation of autotoxic catecholamine metabolites, and augments amphetamine effects in vivo". Issue 4 (28th June 2021) - Masato, Anna; Bubacco, Luigi; Greggio, Elisa
Abstract: Dopamine dyshomeostasis is a driving factor of nigrostriatal degeneration in Parkinson's disease (PD). Accumulation of cytosolic dopamine at striatal projections results in the buildup of autoxidation products, which generates protein adducts and exacerbate oxidative stress. Moreover, an excessive rate of dopamine degradation results in accumulation of 3, 4‐dihydroxyphenylacetaldehyde (DOPAL), a toxic metabolite which rapidly reacts with other proteins. These events lead to protein misfolding and cross‐linking as well as mitochondrial and lysosomal dysfunction, the main pathological mechanisms underscoring dopaminergic neuron loss in PD. In this issue of Journal of Neurochemistry, Vecchio et al. generated and characterized a new in vivo model of chronic dopamine accumulation through the overexpression of a hyperactive form of tyrosine hydroxylase (TH‐HI), the rate‐limiting step enzyme in dopamine biosynthesis. At 3–5 months of age, TH‐HI mice displayed increased striatal dopamine content, exacerbated dopamine catabolism, and augmented responses to amphetamine. This correlated with enhanced oxidative stress and DOPAL buildup, highlighting a catechol‐induced neurotoxic vicious cycle that may anticipate a parkinsonian‐like phenotype in aged mice. This novel TH‐HI animal model represents an exciting new tool to unravel the molecular mechanisms underlying dopamine disequilibrium, catecholamine autotoxicity, and neurodegeneration in PD. Abstract : Dopamine dyshomeostasis is a driving factor of nigrostriatal degeneration in Parkinson's disease. Uncontrolled cytosolic dopamine accumulation results in enhanced oxidative stress, buildup autoxidation products and reactive metabolites, highlighting a catechol‐induced neurotoxic vicious cycle that may anticipate dopaminergic neuron loss. In this Editorial Highlight, we discussed the new in vivo model generated by Vecchio et al., which displays chronic dopamine accumulation through the overexpression of a hyperactive form of tyrosine hydroxylase. At 5‐month age, the tyrosine hydroxylase‐overexpressing (TH‐HI) mouse recapitulates the early signs of dopamine disequilibrium at the striatum, which will be interesting to further characterize in aged mice.